Defense performance analysis: social network analysis - Sasaki, K. (Journal of Human Sport & Exercise, 2015)
This article discusses about the defense performance analysis of rugby union and introduces some analysis approaches. Rugby World Cup is a rugby union tournament contested every four years between the top international teams and is one of the largest international sporting events in the world, like FIFA-WC, The Olympic Games and the Tour de France. The Seventh tournament is going to held in Japan in 2019. After watching the three evidences, we will present some analytical approaches. Data were derived from 20 matches of close and balanced scores (under 20 points: results from cluster analysis according to game final score differences of 40 pool matches in 2011RWC). In these day`s rugby union games, the point balance under 20 points might be comparatively valid value as closed game. Double tackle contributor`s mapping by force-directed placement (degree centrality) at 2011 Rugby World Cup close games in pool matches. Centering Resonance Analysis would be one strong tool for understanding the total relationship structure of network graph, especially when the numbers of vertex has increased and complicated. Network analysis would be one cruel for understanding the complex sport scenes. We hope to keep discussing over the 2019 RWC / 2020 Tokyo Olympic games. we desire for making sport family in whole world and of course in Asian Friends.